Identifikasi Minat Karir dengan menggunakan Holland Test terhadap Prestasi Akademik Mahasiswa - Bantam, Dian Juliarti; Pradana, Wina Dryan (Universitas Muhammadiyah Metro, 2024)
The research objective is to identify career interests in student academic achievement. In this research, students' career interests will be measured using John Holland's 60-item career interest test tool, which divides interests into six categories, known as RIASEC Models: realistic, investigative, artistic, social, enterprising, and conventional. Departing from the existing urgency, this research aims to identify career interests using the Holland test tool for student academic achievement. This research method is quantitative correlational with two variables: Career Interest and Academic Achievement. The sample selection technique uses purposive sampling, with the criteria being students in semester six and taking Career Education courses. The subjects in this research were 146 students, of which psychology was 50 (34.2%), law was 33 students (22.6%), management was 28 students (19.2%), and accounting was 35 students (24%). The hypothesis developed in this research is that there is a relationship between career interests and student academic achievement. SPSS was used to analyze the results using an analysis technique in the form of the Fisher Exact Test. The result of this research is that the hypothesis is accepted, where there is a relationship between career interest and the academic achievement of FES Unjaya students. Data analysis obtained a sig value of 0.001 (p<0.05).